Laboratory validation of formal concept analysis of the methylation status of microarray-detected genes in primary breast cancer - Samar K Kassim; Hanan H Shehata; Marwa M Abou-Alhussein; Maha M Sallam; Islam Ibrahim Amin (Tumor Biology)
Breast cancer is the leading cause of cancer-related mortality. DNA methylations play important roles in cancer development and progression. Formal concept analysis was previously utilized for data mining hypermethylated and hypomethylated genes in breast cancer molecular subtypes in illumina methylation–based microarray database, to laboratory validate their outputs; HS3ST2 (heparan sulfate d -glucosaminyl 3-O-sulfonyl transferase-2) and MUC1 (mucin-1) were retrieved. Both play important roles in progression and invasion of breast cancer. The methylation status of both genes was laboratory validated using methylation-based polymerase chain reaction in breast cancer subtypes luminal A (early stages) and luminal B (late stages) in comparison with benign conditions and normal breast to conclude their roles in tumor invasion and to validate the newly developed algorithm (formal concept analysis). Significant cancer-specific hypermethylation of HS3ST2 was detected in luminal B (chi square = 30.6, p = 0.000), while significant cancer-specific hypomethylation of MUC1 was detected in luminal B (chi square = 30.5, p = 0.001) breast cancer. The median levels of the percentage of methylated allele of both genes were significantly discriminative between luminal A and luminal B subtypes and benign and healthy control groups. Detection of MUC1 and HS3ST2 promoter methylation status appears to be useful molecular markers for assessing the progressive state of the disease and could be helpful in discriminating breast cancer molecular subtypes. These results validate the methylation-based microarray analysis, thus trust their output in the future.